2022
DOI: 10.1002/adma.202207847
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioelectronics with a Remodellable Matrix for Long‐Term Tissue Integration and Recording

Abstract: Bioelectronics hold the key for understanding and treating disease. However, achieving stable, long‐term interfaces between electronics and the body remains a challenge. Implantation of a bioelectronic device typically initiates a foreign body response, which can limit long‐term recording and stimulation efficacy. Techniques from regenerative medicine have shown a high propensity for promoting integration of implants with surrounding tissue, but these implants lack the capabilities for the sophisticated record… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Recent work has shown that increased miniaturization and a minimalistic approach to the interface can further decrease the immune response associated with an implant placement (Figure 3a). Structures with maximum feature sizes in the range of cell diameters (<20 μm) appear to show limited foreign body responses, [46,47] contingent on a minimally-damaging surgical approach. However, the placement of such structures can be challenging due to their size.…”
Section: Integration Interfacing and Interaction-the Next Generation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that increased miniaturization and a minimalistic approach to the interface can further decrease the immune response associated with an implant placement (Figure 3a). Structures with maximum feature sizes in the range of cell diameters (<20 μm) appear to show limited foreign body responses, [46,47] contingent on a minimally-damaging surgical approach. However, the placement of such structures can be challenging due to their size.…”
Section: Integration Interfacing and Interaction-the Next Generation ...mentioning
confidence: 99%
“…[ 58 ] These directions are only subtly different from a design perspective and can theoretically be used in tandem. Recent work has shown successful integration of devices using both these mechanisms, showing successful tissue ingrowth [ 46 ] and even successful cell transplantation and interfacing, [ 59 ] with other studies focusing on nerve regeneration through implanted electrodes [ 60 ] or fully tissue engineered structures. [ 61 ] With the recent approval of translational work in tissue engineered fields, this approach is likely to gain traction as an important upcoming design method for new bioelectronics.…”
Section: Integration Interfacing and Interaction—the Next Generation ...mentioning
confidence: 99%
“…Implants were fabricated using photolithographic techniques for flexible electronic devices 12 . PaC, from dichloro-p-cyclophane (Specialty Coating Systems, Indianapolis, IN, USA) was deposited (Specialty Coating Systems Labcoater -Specialty Coating Systems, Indianapolis, IN, USA) at a 2 μm thickness onto a Si wafer.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Advances in materials and microfabrication strategies have opened new opportunities to interface with the nervous system. The last decade has seen the development of a wide range of multielectrode array implants interfacing with nervous tissue in novel ways 9 , with a growing focus on soft and flexible constructions to improve tissue interface quality and long-term stability [9][10][11][12][13][14] , as well as high-performance recording microelectrode materials 11 . However, most of these technologies have focused on the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle implantation models allow assessment of both FBR and tissue healing, unlike subcutaneous implantation models. [32] Poly(etheretherketone) (PEEK) was selected to model a clinically acceptable, non-biodegradable poly-mer that has no toxicity but triggers a relatively strong inflammatory response and FBRs. [33][34][35][36] We propose that the PSLmultilayer coating represents a simple and versatile technology to limit chronic inflammation and fibrotic scarring associated with implanted devices as well as to promote tissue healing.…”
Section: Introductionmentioning
confidence: 99%